ANALISIS KUALITAS AIR DAN TEKSTUR SEDIMEN PADA DAERAH TERSEDIMENTASI DI LAGUNA SEGARA ANAKAN CILACAP - Lilik Kartika Sari; Luky Adrianto; Kadarwan Soewardi; Agus S Atmadipoera; Endang Hilmi (Journal Omni-Akuatika, 2015)
This paper provides an overview of the environmental quality of areas affected by sedimentation on a lagoon. Observations made on water conditions as well as the texture of sedimennya. The observed water quality parameters is salinity, pH, NO3-N, PO4-P, COD and BOD. The observation is performed also on sediment texture on the 6 stations that represents the condition of the lagoon. The addition of LANDSAT Imagery based on land area in the province of Laguna Segara Saplings in two decades is of 823,9 ha per year.Keywords : sedimentation, the quality of the environment